Current Situation of Telehealth in Chronic Disease Care in the Czech Republic - Hašek, Milan (2017)
The Impact of chronic diseases in high income countries is very high and so it is in the Czech Republic as one of those countries. Chronic diseases are therefore a huge issue that needs to be tackled. One of the ways how to fight those diseases may lay in technologies such as telehealth. Telehealth has the ability to efficiently remove the time and distance barrier in receiving health services, which can be very useful nowadays when the number of chronic patients is increasing. The Czech Republic as a high-income country is therefore a country where telehealth solution could improve the situation of chronic disease care. Hence, to research this area following research question was developed: What is the current state/situation of telehealth in chronic disease care in the Czech Republic?The thesis has two parts. The first theoretical part is done through comprehensive and extensive research of literature providing strong ground for the practical part of the thesis. The practical part is researched through the field work combining personal interviews, email and telephonic conversations. The evaluation of the finding is done with qualitative content analysis. The analysis uses quotations, paraphrasing and generalisations from which the findings are deducted. The importance of the topics is based on open coding and categorizing.The results showed that Czech Republic is still in the beginning of wide usage of telehealth technologies. Even though there are successful projects and programs going on it is still based mostly on volunteerism or as a hobby and are self-funded or funded by grants. The reason is that there are several barriers that prevents further developments. Among those is mostly the unwillingness of health insurance companies to reimburse those services and the patients to pay for them themselves. Another problem is that the doctor don’t want to use telehealth solutions.